PENGARUH PROMOSI PENJUALAN, KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP LOYALITAS MELALUI KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (PADA KONSUMEN KEDAI PESENKOPI JL. SUNAN KALIJAGA N0. 8, SUMBERSARI, KEC. LOWOKWARU, KOTA MALANG, JAWA TIMUR.) - Lalu Wahyu Azazi; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT The development of the culinary world that is happening in the world is growing rapidly, both culinary oriented to food or drink. Everyone who is involved in the business world competes to be the best and the foremost for the products that have been made to attract the attention of consumers. Customers are an important part of the business world, without any customers in the business, of course there will be no business processes that occur. Therefore customers are very influential in the wheels of business and business. This study aims to explain the effect of sales promotion, service quality and product quality on loyalty through customer satisfaction as an intervening variable. In a business process, the customer would want to be well served by the merchant and the customer will be satisfied if his wishes or expectations are met when buying and feeling the product or service that is felt. With such an impact, it is expected that customers will be loyal to use the product or service that they feel is good. The purpose of this study is to find out and analyze the effect of sales promotion, service quality and product quality on loyalty through customer satisfaction as an intervening variable. The method used is quantitative. The method of data analysis in this study is quantitative and technical analysis methods using path analysis using IBM Version 21 SPSS (statistical product and service solution) software. The sample used was 80 people. Data collection is done by collecting questionnaires with purposive sampling technique. Data analysis uses path analysis where Sales Promotion as X1, Service Quality X2, X3 Product Quality, Z Customer Satisfaction and Z Loyalty. The results of this study indicate that the X test on Y is known that t count Sales Promotion on customer satisfaction is 0.217, t count Service Quality for Customer Satisfaction of 0.720 and t count Product Quality Against Customer Satisfaction of 0.100 with a significance level of both variables <0.05 , then this shows that Sales Promotion, Service Quality and Product Quality directly influence Customer Satisfaction. Thus H0 is rejected and Ha is accepted which states that Sales Promotion, Service Quality and Product Quality have a significant effect on Customer Satisfaction. X test against Y is known that that t Sales Sales to customer Loyalty is 6.157, t calculate Service Quality to Customer Loyalty of 3.520 and t count Product Quality Against Customer Loyalty is 0.936 with a significance level of both variables of <0.05, then this shows that Sales Promotion, Service Quality and Product Quality directly influence Customer Loyalty. Thus H0 is rejected and Ha is accepted which states that Sales Promotion, Service Quality has a significant effect on Customer Loyalty but is not significant by the Product Quality variable on Customer Loyalty. The Z test on Y is known that t count Customer satisfaction with Customer Loyalty is 14.873 with a significance level of both variables of <0.05, then this indicates that Customer Satisfaction directly affects Customer Customer Loyalty. Thus H0 is rejected and Ha is accepted which states that Customer Satisfaction has a significant effect on Customer Loyalty. Keywords: sales promotion, service quality, product quality, customer satisfaction, customer loyalty.